PENDEKATAN KEDOKTERAN KELUARGA PADA DIABETES MELLITUS DENGAN KOMPLIKASI KRONIS - Silitonga, Yunico S.M.; Fitri, Zayanda; Karimah, Anjani D.; Hendratno, Ergita F.; Devanka, Kennygya A.A.; Puryani, Noorma Z.; Hikmah, Wulan N.; Larasari, Andira; Satyasari, Daniella (Jurnal Pengabdian Masyarakat Trimedika, 2024)
Indonesia sees an annual rise in the prevalence of diabetes mellitus. Diabetes mellitus that is not managed can have negative effects on quality of life and cause problems. This activity aims to analyze and identify risk factors for people with diabetes mellitus, especially regarding the role of family environment on the development of the disease and the onset of complications, then educate them and their families about the importance of controlling blood sugar through regular treatment and dietary regulation. Data was taken using primary data during visits to patients' homes in Krendang Village. A 48-year-old lady reported that her activities were being interfered by acute pain in both hands and feet, which had become increasingly worse over the previous year. Upon physical examination, there was a blood pressure reading of 150/90 mmHg, a body mass index of 30.85 kg/m2, and an epigastric discomfort. Additionally, there was positive CVA knocking pain and wounds on the right and left foot toes. A neurological examination revealed diminished Achilles reflexes and paresthesia in the socks and gloves. The results of the GDS test were 216 mg/dL. An essential component of controlling diabetes mellitus is education about maintaining blood sugar levels through consistent treatment as well as diet. A higher quality of life can be achieved by diabetes mellitus patients with family support.